Entornos virtuales y su incidencia en el desarrollo de habilidades informáticas de los estudiantes del tercero de bachillerato de la Unidad Educativa Padre Marcos Benetazzo periodo 2021 – 2022 - Ferrin Romero, Danna Nicole (2022)
The present case study consisted in making a first approach to the theories on the use of the Virtual Learning Environment is a proposal that reinforces the academic performance of the students, the influence of the virtual education of significant learning is positive, and for this reason constitutes the fundamental objective for the elaboration of the proposal, under a methodological guide approach that helps in the performance of the students. Being the general objective of the project to analyze the incidence of the application of the Virtual Learning Environment and its incidence the incidence of the application of virtual environments in the development of computer skills of the students of the third year of high school of the Padre Marcos Benetazzo educational unit, the same one that is located in the Province of Los Ríos, Babahoyo Canton. The methodology that was applied in this research was the quantitative method, with a documentary study, bibliographical research, with the application of surveys for data collection and their respective tabulation. The information collection instruments were analyzed, with which it was concluded that third-year high school students have a high development of digital competence, therefore the student is encouraged to continue exploring the technological environment.